ANALISIS EKSERGI DAN OPTIMASI PEMBANGKIT LISTRIK TENAGA PANAS BUMI LAHENDONG UNIT-2 - Armando Ariakta Aloanis; Heindrich Taunaumang; Alfrie Rampengan; Jeferson Polii (Jurnal FisTa : Fisika dan Terapannya, 2021)
Geothermal development is carried out by increasing the efficiency of existing generators. In this study, geothermal development at the Lahendong Unit-2 geothermal power plant is carried out by conducting exergy analysis and optimizing geothermal plant efficiency using a genetic algorithm by adjusting the pressure on the separator. Exergy calculations and optimization of genetic algorithms, using the Python programming language with the help of libraries such as PyXSteam, Pandas, Numpy, matplotlib, random, and time. Exergy flow and efficiency are calculated on the components of the separator, turbine, condenser, cooling tower, and the entire plant. The amount of exergy that enters the generator from geothermal fluids is 28882.73 kW. The amount of exergy that comes in produces an output power of 13,000 kW with an overall efficiency of the generator is 45.010%, and the amount of exergy from brine is 1794.11 kW. Optimization using the genetic algorithm method produces the most optimal output power value of 13035,480445 kW at a separator pressure of 10.4025 bar. The increased quality of the steam generates this increase in power so that the mass flow rate of the steam that rotates the turbine becomes more than before.